Impact of trade and structural change on the sub-Saharan African economies - Paul I. Ko; Ryo Makioka; Karim Nchare (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Sub-Saharan African economies have experienced accelerated economic growth in the past two decades. In this paper we study the impact of trade-induced structural change on employment and value-added shares in sub-Saharan African economies. We find that sub-Saharan African economies have increasingly become net importers of manufacturing goods. Similar to other countries, an increase in manufacturing imports negatively impacts manufacturing employment shares. In contrast, an increase in exports positively impacts agricultural employment shares. We further find that neither exports nor imports affect value-added shares in manufacturing. Based on our empirical findings, we propose a quantitative trade model that explains how an increase in trade can reduce employment shares in the manufacturing sector, leading to structural transformation and potentially explaining Rodrik's 'African manufacturing puzzle'.
Keywords: H6; O14; O55; 330; trade; structural change; sub-Saharan African economies